Legal Implications of Marriage Agreements Regarding Separation of Joint Property Following Constitutional Court Decision Number 69 of 2015 : Case Study Number 49/Pdt.P/2020/PA.Tgrs - Shiva Durrotu Luthviah; M. Nassir Agustiawan; Mohammad Hifni (Yayasan pendidikan dzurriyatul Quran, 2025)
Constitutional Court Decision Number 69/PUU-XIII/2015 has provided a new legal basis for interpreting Article 29 paragraph (1) of Law Number 1 of 1974 concerning Marriage, which previously only allowed the creation of marriage agreements before or during the marriage. The purpose of this study is to analyze the legal impact of allowing marriage agreements after the marriage has taken place, as a consequence of Constitutional Court Decision No. 69/PUU-XIII/2015, and to examine how this new norm is applied in judicial practice through a case study of Case No. 49/Pdt.P/2020/PA. Tgrs at the Tigaraksa Religious Court. The research uses a normative juridical approach with primary data sources in the form of court decisions and legislation, as well as secondary data such as legal doctrine, theories on agreements and legal certainty, and the results of interviews with relevant law enforcement officials. The findings of the study show that the Constitutional Court's decision expands the application of the principle of freedom of contract contained in Article 1338 of the Civil Code and affirms that married couples have the constitutional right to regulate their civil relations through agreements, including those concerning joint property, without being bound by the time of creation before marriage. In case 49/Pdt.P/2020/PA.Tgrs, the Panel of Judges granted the ratification of the marriage agreement because it fulfilled the elements of legality and did not cause harm to third parties. This shows that the norms resulting from the Constitutional Court's decision have been accepted as a valid source of law in court practice. The legal consequences of marriage agreements made after marriage include the need for new guidelines in the judicial and notarial fields, the importance of the ratification process in court, and the guarantee of legal protection for third parties who may be affected. Although the change in norms has taken place, its implementation still faces obstacles, mainly due to the limited understanding of law enforcement officials and the absence of official technical provisions from the Supreme Court or the Ministry of Religious Affairs as a basis for implementation at the national level.